Activation of mGluR1 negatively modulates glutamate-induced phase shifts of the circadian pacemaker in the mouse suprachiasmatic nucleus - Yoon Sik Kim; C Justin Lee; Ji-Hyeon Kim; Young-Beom Kim; Christopher S. Colwell; Yang In Kim (Neurobiology of Sleep and Circadian Rhythms, 2023)
In mammals, photic information delivered to the suprachiasmatic nucleus (SCN) via the retinohypothalamic tract (RHT) plays a crucial role in synchronizing the master circadian clock located in the SCN to the solar cycle. It is well known that glutamate released from the RHT terminals initiates the synchronizing process by activating ionotropic glutamate receptors (iGluRs) on retinorecipient SCN neurons. The potential role of metabotropic glutamate receptors (mGluRs) in modulating this signaling pathway has received less attention. In this study, using extracellular single-unit recordings in mouse SCN slices, we investigated the possible roles of the Gq/11 protein-coupled mGluRs, mGluR1 and mGluR5, in photic resetting. We found that mGluR1 activation in the early night produced phase advances in neural activity rhythms in the SCN, while activation in the late night produced phase delays. In contrast, mGluR5 activation had no significant effect on the phase of these rhythms. Interestingly, mGluR1 activation antagonized phase shifts induced by glutamate through a mechanism that was dependent upon CaV1.3 L-type voltage-gated Ca2+ channels (VGCCs). While both mGluR1-evoked phase delays and advances were inhibited by knockout (KO) of CaV1.3 L-type VGCCs, different signaling pathways appeared to be involved in mediating these effects, with mGluR1 working via protein kinase G in the early night and via protein kinase A signaling in the late night. We conclude that, in the mouse SCN, mGluR1s function to negatively modulate glutamate-evoked phase shifts.